Հայաստանի Հանրապետությունում հանրային կապերի (PR) ոլորտի ձեռքբերումներն ու մարտահրավերները - Ավետիսյան Աստղիկ (YSU Journal of International Affairs, 2018)
Public opinion creates reality in a democratic system. Therefore, the role of Public Relations specialists is invaluable in all spheres of the modern world, from policy to culture, from state to private. Public relations is directly connected with the democracy level in the country. While PR is perceived as a “well developed” (but at the same time very dynamic and always changeable) science in the West, it is quite a new profession at the stage of its development in independent Armenia. Our researches show that along with the fast-changing world of information and communications technology, the tools and techniques for drawing public attention have also been changed.